The impact of healthcare system quality and economic factors on the older adult population: a health economics perspective - Iuga, Iulia Cristina; Nerişanu, Raluca Andreea; Iuga, Horia (Frontiers in Public Health, 2024)
Purpose: This study investigates the influence of economic conditions, healthcare system capacity, and health-related variables on the proportion of the elderly population (Population ages 65 and above) in European Union countries. It aims to identify how factors such as GDP, unemployment, inflation, healthcare expenditure, hospital bed availability, and the prevalence of chronic diseases impact the aging demographic.Methods: This study explores the dynamic interactions and temporal relationships between economic stability, healthcare capacity, chronic disease prevalence, and demographic aging patterns. The research employs a mixed-method approach, utilizing System GMM and wavelet coherence analysis on panel data from 27 EU countries between 2000 and 2021.The findings reveal significant positive associations between economic prosperity and healthcare resources with the size of the elderly population. Increased GDP, efficient healthcare spending, and hospital bed availability are positively correlated with a larger elderly demographic. In contrast, high unemployment and inflation are linked to negative outcomes for the elderly population, reducing available resources and access to healthcare. Wavelet coherence analysis further uncovers how fluctuations in the prevalence of chronic diseases influence aging trends across different periods and frequencies.The study highlights the importance of integrated economic and healthcare policies to support the growing elderly population. Ensuring economic stability, enhancing healthcare infrastructure, and effectively managing chronic diseases are essential for improving quality of life and promoting sustainable aging in EU societies.